Transformation of Hawaiian Music Ensemble Function at Germita Bukit Moria Tule Church - Sirait, Markus Bona Tangkas; Saliareng, Riandli; Sumenda, David (Peneliti.net, 2025)
This research examines the changing functions and forms of Hawaiian music ensembles in the Tule Village community, particularly in the context of religious worship. Initially, it functioned as entertainment at weddings and traditional events. Today, however, Hawaiian music is an integral part of worship at Germita Bukit Moria Tule. The purpose of this study is to describe the changes in the function of Hawaiian music ensembles in the Tule village community and to describe the form of Hawaiian music ensembles. This research provides insight into the changing functions of music in different cultural and religious contexts. This research uses a qualitative method with a case study approach. The data collection techniques used were interviews, observation, literature study, and documentation as data sources. Determination of informants was made using the snowball sampling method. The data analysis techniques used include data validity, data transcription, data categorization, content analysis, data interpretation, data testing, and conclusion drawing. The results analyzed significant transformations in the use of Hawaiian music in Tule Village, where this music has been adapted in the ecclesiastical context by GERMITA Bukit Moria Tule. Hawaiian music plays an important role in creating profound spiritual experiences and enriching the spiritual and social dimensions of worship. The integration of Hawaiian music elements in church worship shows that local culture can synergize with spirituality, resulting in a more meaningful and profound worship experience in a local context that enriches the culture.